PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MTS MUHAMMADIYAH 20 NATAL - Walidatul 'Ulya; Muhammad Zuhaery; Suyatno Suyatno (Jurnal Manajemen Pendidikan, 2026)
The principal plays a crucial role in promoting quality learning, not only through administrative duties but also through leadership and mentoring of the school community. This study aims to examine the role of the principal in improving the quality of learning at MTs Muhammadiyah 20 Natal. This research employed a qualitative approach with a case study design. The informants consisted of the principal, teachers, and students selected through purposive sampling. Data were collected through observation and in-depth interviews, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that the principal performs six main roles: manager, administrator, supervisor, educator, leader, and motivator. The principal is able to manage learning resources adaptively, ensure orderly administration, conduct continuous supervision, and encourage active and meaningful learning despite limited facilities and infrastructure. In addition, the principal provides role models and motivation to teachers and students, which has an impact on improving teaching quality and student learning motivation. These findings indicate that comprehensive and adaptive leadership contributes significantly to improving the quality of learning.